Adiponectin-derived active peptide ADP355 exerts anti-inflammatory and anti-fibrotic activities in thioacetamide-induced liver injury - Wang, Huafeng (Sci Rep, 2016)
Adiponectin is an adipocyte-derived circulating protein with beneficial effects on injured livers. Adiponectin-deficient (adipo(−/−)) mice develop enhanced liver fibrosis, suggesting that adiponectin could be a therapeutic target for liver injury. In the present study, we investigated the protective role of ADP355, an adiponectin-based active short peptide, in thioacetamide (TAA)-induced acute injury and chronic liver fibrosis in mice. ADP355 remarkably reduced TAA-induced necroinflammation and liver fibrosis. ADP355 treatment increased liver glycogen, decreased serum alanine transaminase and alkaline phosphatase activity, and promoted body weight gain, hyper-proliferation and hypo-apoptosis. In addition, ADP355 administration suppressed the TAA-induced activation of hepatic stellate cells and macrophages in the liver. These were associated with the inactivation of TGF-β1/SMAD2 signaling and the promotion of AMPK and STAT3 signaling. Sensitivity of adipo(−/−) mice to chronic liver injury was decreased with ADP355. In conclusion, ADP355 could mimic adiponectin’s action and may be suitable for the preclinical or clinical therapy of chronic liver injury.